IL-6 deficiency promotes colitis by recruiting Ly6Chi monocytes into inflamed colon tissues in a CCL2-CCR2-dependent manner - Cao, Qiuhua; Lin, Yanting; Yue, Chongxiu; Wang, Yue; Quan, Fei; Cui, Xinmeng; Bi, Ran; Tang, Xinying; Yang, Yong; Wang, Chen; Li, Xianjing; Gao, Xinghua (European journal of pharmacology, 2021)
Interleukin 6 (IL-6) is a pleiotropic cytokine that is elevated in inflammatory bowel disease. However, the role of IL-6 deficiency in colitis is not well-defined. Some IL-6 and IL-6 receptor antagonists are associated with severe gastrointestinal immune adverse effects, but the mechanisms of the effects are not clear. This study aimed to investigate the effect of IL-6 in ulcerative colitis in Il6−/− mice. Results indicated that physiological deficiency of IL-6 promoted the development of colitis. Moreover, IL-6 deficiency significantly increased the mRNA levels of monocytes chemokine Ccl2 and its receptor Ccr2 in colon tissues. Similarly, the percentage of Ly6Chigh monocytes and neutrophils were increased in the colon of Il6−/− mice. Intestinal crypts more strongly increased the migration of Il6−/− macrophages than wild-type ones. Moreover, Il6−/− macrophages promoted the migration of neutrophils. Most importantly, RS102895, an antagonist of CCR2, diminished chemotaxis of macrophages and inhibited colitis in Il6−/− mice. Collectively, these results indicate that Il6−/− macrophages migrate to inflamed colon tissues and recruit neutrophils, thereby promoting the effect of Il6−/− on colitis. This study expands our understanding on the effect of IL-6 deficiency in colitis and the development of gastrointestinal immune adverse effects. A proposed model illustrating the mechanism of IL-6 deficiency promoting DSS-induced colitis. IL-6 deficiency aggravates DSS-induced colitis by recruiting circulating Ly6Chi monocytes in a CCL2-CCR2-dependent manner to colon tissues. Furthermore, under inflammation conditions, Il6−/− macrophages promote the migration of neutrophils to the colon tissues by secreting neutrophils chemokines, such as CXCL1, CXCL2, and IL-23. The overactivated neutrophils form NETs, which secrete anti-microbial molecules such as MPO. MPO damages intestinal epithelium and aggravates the development of colitis. [Display omitted] •IL-6 physiological deficiency facilitates the development of DSS-induced colitis.•IL-6 deficiency promotes colitis by recruiting Ly6Chi monocytes into inflamed colon tissue CCR2 antagonist blocks the chemotaxis of macrophages and terminate the aggravating colitis in in a CCL2-CCR2-dependent manner.•IL-6-deficient macrophages recruit more neutrophils which secreted MPO, destroy the intestinal epithelium.•This study enlightens our knowledge on the pathology of gastrointestinal immune adverse effects of IL-6 antagonists.